PERBEDAAN PEMBELAJARAN COOPERATIVE MIND MAPPING DAN COOPERATIVE SCRIPT PADA MATERI DIMENSI TIGA TERHADAP KEMAMPUAN SPASIAL DAN DISPOSISI MATEMATIKA SISWA - Rahmat Fauzi Siregar; Pargaulan Siagian; Hamidah Nasution (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
The aims of this research were : (1) Knowing the significant differences between the spatial abilities of students taught by cooperative mind mapping learning with students taught by learning cooperative scripts, (2) Knowing the significant differences between the mathematical dispositions of students taught using cooperative mind mapping models and students. which is taught by learning cooperative Script, (3) Determining whether there is an interaction between cooperative mind mapping learning and cooperative script learning with students' spatial abilities and mathematical disposition abilities. This research is a quasi-experimental research. The population in this study consisted of all students of class XII MAN KHA Dahlan Sipirok, totaling 120 students, by taking samples of two classes totaling 34 students. Data analysis was performed using two-way ANOVA. The results of this study indicate that (1) the spatial ability of students taught by cooperative mind mapping learning is higher than students taught by cooperative script learning, (2) the mathematical disposition of students taught by cooperative mind mapping learning is higher than students taught by cooperative learning. Script, (3) There is no interaction between learning and students 'initial mathematical abilities on students' spatial abilities.